2014
DOI: 10.1016/j.intfin.2014.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Index revisions, systematic liquidity risk and the cost of equity capital

Abstract: This study investigates the impact of FTSE100 index revisions on firms' systematic liquidity risk and the cost of equity capital. We show that index membership enhances all aspects of liquidity, whereas stocks that leave the index exhibit no significant liquidity change. We also show that the liquidity risk premium and the cost of equity capital decline significantly after additions, but do not exhibit any significant change following deletions. The control sample analysis indicates that observed decline in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 58 publications
(80 reference statements)
0
10
0
Order By: Relevance
“…The result is contrary to what should have happened otherwise; that is, the COEC should have declined for inclusion firms and increased for exclusion firms. Further, this result is inconsistent with (Baran & King, 2012;Becker-Blease andPaul, 2006, 2010;Biktimirov & Li, 2014;Elliott et al, 2006;Hegde & McDermott, 2003;Mazouz et al, 2014) who report that, for inclusion firms, an increase in liquidity leads to decrease in the cost of capital, and for exclusion firms, a decrease in liquidity leads to an increase in the cost of capital.…”
Section: Model Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…The result is contrary to what should have happened otherwise; that is, the COEC should have declined for inclusion firms and increased for exclusion firms. Further, this result is inconsistent with (Baran & King, 2012;Becker-Blease andPaul, 2006, 2010;Biktimirov & Li, 2014;Elliott et al, 2006;Hegde & McDermott, 2003;Mazouz et al, 2014) who report that, for inclusion firms, an increase in liquidity leads to decrease in the cost of capital, and for exclusion firms, a decrease in liquidity leads to an increase in the cost of capital.…”
Section: Model Resultsmentioning
confidence: 83%
“…The results of inclusions and exclusions are contrary to the previous studies of Baran and King (2012) who reported a decrease in the COEC for the inclusion firms and an increase in the COEC for the exclusion firms of the S&P 500 index. Similarly, Mazouz et al (2014) also reported a decline in the COEC post-inclusion and no change in the COEC post-exclusion for the FTSE 100 index revisions. Moreover, the results of the COEC are in accordance with the results reported for stock liquidity in Section "Liquidity Effects of Stock Index Revisions" of this article.…”
Section: Univariate Analysis Of Coec Changesmentioning
confidence: 84%
See 2 more Smart Citations
“…Prior work provides evidence that the index revisions significantly impact the stock performance. Studies (Baran & King, 2012; Becker-Blease & Paul, 2006, 2010; Biktimirov & Li, 2014; Chan et al, 2013; Chen et al, 2004; Dhillon & Johnson, 1991; Edmister et al, 1996; Elliott et al, 2006; Fernandes & Mergulhão, 2016; Gregoriou, 2011; Gregoriou & Nguyen, 2010; Hegde & Mc Dermott, 2003; Hrazdil, 2009; Kamal, 2014; Kot et al, 2015; Mazouz et al, 2014; Miller & Ward, 2015; Sadeghi, 2011) have analysed the effect of index reorganization on the liquidity, cost of equity capital and abnormal rate of return in the international context. Afego (2017) presents a detailed review of studies related to changes in index compositions.…”
Section: Introductionmentioning
confidence: 99%